2018
DOI: 10.1038/s41598-017-18433-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-34 and CSF-1 display an equivalent macrophage differentiation ability but a different polarization potential

Abstract: CSF-1 and IL-34 share the CSF-1 receptor and no differences have been reported in the signaling pathways triggered by both ligands in human monocytes. IL-34 promotes the differentiation and survival of monocytes, macrophages and osteoclasts, as CSF-1 does. However, IL-34 binds other receptors, suggesting that differences exist in the effect of both cytokines. In the present study, we compared the differentiation and polarization abilities of human primary monocytes in response to CSF-1 or IL-34. CSF-1R engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 41 publications
7
147
0
1
Order By: Relevance
“…CSF-1 and IL-34 both bind to CSF1R and are both expressed in the brain, but the cell signaling events differ between the two ligands. 44,45 We observed increased CSF-1 mRNA levels in the brains of PD patients compared to age-matched controls ( Figure 1B), whereas we found no difference in IL-34 mRNA levels ( Figure 1C). Further, CSF-1 gene expression and protein levels were increased in the SN in animal models of PD, suggesting that CSF-1 is the predominant factor in PD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…CSF-1 and IL-34 both bind to CSF1R and are both expressed in the brain, but the cell signaling events differ between the two ligands. 44,45 We observed increased CSF-1 mRNA levels in the brains of PD patients compared to age-matched controls ( Figure 1B), whereas we found no difference in IL-34 mRNA levels ( Figure 1C). Further, CSF-1 gene expression and protein levels were increased in the SN in animal models of PD, suggesting that CSF-1 is the predominant factor in PD.…”
Section: Discussionmentioning
confidence: 66%
“…We found that samples from PD patients had higher gene expression of CSF1R and significantly higher CSF-1 gene expression compared to age-matched controls, whereas IL-34 was not different between the groups (Figure 1). 44,45 We observed increased CSF-1 mRNA levels in the brains of PD patients compared to age-matched controls ( Figure 1B), whereas we found no difference in IL-34 mRNA levels ( Figure 1C). We tested this hypothesis by utilizing an LPS inflammation model and an acute MPTP neurotoxicity model.…”
mentioning
confidence: 66%
“…47 IL-34 is a newly identified cytokine that activates the colony-stimulating factor-1 receptor (CSF-1R). 48 Galligan and Fish 49 show that in vitro fibrocyte precursors treated with IL-34 induce the proliferation of fibrocytes-mediated by the…”
Section: Factors That Promote and Inhibit Fibrocyte Differentiationmentioning
confidence: 99%
“…CSF1 and IL‐34 are the two endogenous cognate ligands of CSF‐1R, which upon activation stimulates monocyte/macrophage differentiation pattern and the acquisition of a phagocytic phenotype (Boulakirba et al, ). On the other hand, SCF is the ligand of c‐Kit, which in peripheral tissues is mainly expressed in mast cells (Iemura, Tsai, Ando, Wershil, & Galli, ).…”
Section: Introductionmentioning
confidence: 99%